2004
DOI: 10.1111/j.1747-6593.2004.tb00514.x
|View full text |Cite
|
Sign up to set email alerts
|

Constructed Wetlands for Minewater Treatment: Environmental Benefits and Ecological Recovery

Abstract: The ecology of the River Pelenna (in South Wales) was impoverished by polluted discharges from abandoned coal mines. A series of passive constructed wetlands was created in order to treat these discharges and to improve the ecology of the river. A three‐year Environment Agency R&D project investigated the performance, environmental benefits and sustainability of the constructed wetlands. It showed that the treatment systems were removing most of the iron contamination. In the reaches downstream from the minewa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…In this study, downstream (sites S3–S5) benthic invertebrate diversity showed a 3-fold improvement over a 7-year period following 2003, although it has not yet reached the diversity present in the non-AMD polluted tributary. Previous assessments of AMD recovery using benthic invertebrates showed a similar improvement; however, those systems were less severely impacted than the Afon Goch, with a pre- and post- remediation pH of 5.5 and 7.5 respectively, and lower metal concentrations. , This study on the Afon Goch therefore shows that even in severely polluted and acidic systems the benthic fauna can show relatively rapid and substantial recovery once efficient remediation measures are implemented.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…In this study, downstream (sites S3–S5) benthic invertebrate diversity showed a 3-fold improvement over a 7-year period following 2003, although it has not yet reached the diversity present in the non-AMD polluted tributary. Previous assessments of AMD recovery using benthic invertebrates showed a similar improvement; however, those systems were less severely impacted than the Afon Goch, with a pre- and post- remediation pH of 5.5 and 7.5 respectively, and lower metal concentrations. , This study on the Afon Goch therefore shows that even in severely polluted and acidic systems the benthic fauna can show relatively rapid and substantial recovery once efficient remediation measures are implemented.…”
Section: Discussionsupporting
confidence: 57%
“…Although a number of studies have detailed the negative impact of AMD on river biota, only a few have looked at biotic recovery following remediation. 37 In this study, downstream (sites S3−S5) benthic invertebrate diversity showed a 3-fold improvement over a 7-year period following 2003, although it has not yet reached the diversity present in the non-AMD polluted tributary. Previous assessments of AMD recovery using benthic invertebrates showed a similar improvement; however, those systems were less severely impacted than the Afon Goch, with a pre-and post-pH of 5.5 and 7.5 respectively, and lower metal concentrations.…”
Section: ■ Discussionmentioning
confidence: 51%
See 2 more Smart Citations